Тhе Necessity of Vitamin D for Fertility in Women of Reproductive Age (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Vitamin D deficiency is very common in women of reproductive age. Vitamin D deficiency is very common in women of reproductive age [1,2,4]. The physiological role of vitamin D in reproduction remains controversial. In humans, low maternal vitamin D levels have been associated with adverse maternal and fetal outcomes, including preeclampsia [3,6,7], gestational diabetes mellitus, low for gestational age, and low birth weight. Several studies have reported that vitamin D deficiency affects both insulin secretion and insulin resistance. Insulin resistance is a hallmark of obesity, one of the most common endocrine diseases affecting women of reproductive age [5,8].